Northern extension of Lesueurigobius friesii (Malm, 1874) (Pisces: Gobiidae) distribution and the gobiid diversity decline along the Norwegian coast - Kovačić, Marcelo (Array, 2019)
Lesueurigobius friesii was collected in Eidsfjorden, Sognefjorden, Norway, extending its known distribution range north as the new northernmost locality of this species. Globally, the northernmost presence of gobies is along the coast of Norway. Their diversity along the Norwegian coast showed an evident latitude gradient of gobiid diversity with a clear decrease from south to north. The significant regression structural change was found at the 63/64° N latitude band followed by a 36.4% decrease in gobiid species diversity. The species traits of gobiids north of the regression breaking point and those restricted to the south of it were compared. The only significantly more frequent characteristic of species passing north of the regression breaking point is the large depth range that reach down to the shelf break. All species present north of the point, except Thorogobius ephippiatus (that barely passes it) belong to Oxudercinae (i.e. to Pomatoschistuslineage of that subfamily).